Study on the Fast Extension Mechanism of Double-Cavity Shock Absorber with High-Pressure Piston - Xingbo Fang; Hu Chen; Xiaohui Wei; Hong Nie (International Journal of Aerospace Engineering)
Double-cavity shock absorber with high-pressure piston is the core component of the nose landing gear of the carrier-based aircraft, and its fast-extension performance seriously affects the safety of the catapult-assisted takeoff. The design of a carrier-based aircraft in our country is carried out based on the traditional method of fast-extension dynamics, and it is found that the fast-extension capability is larger than designed. This paper analyzes the working principle of the high-pressure piston shock absorber and explains that the high-pressure air cavity pushes the piston rod to extend rapidly, which will cause the cavitation phenomenon in the main oil chamber. Thus, the cavitation in the main oil chamber makes the traditional modeling method of oil-liquid resistance force no longer applicable. Then, the axial force modeling method of shock absorber considering the cavitation effect is proposed. Based on the carrier-based aircraft, the dynamic response of the shock absorber in the process of fast extension is calculated and then it is compared with the calculation results of the traditional dynamic method. It is found that due to the cavitation effect caused by the forced fast extension section of the high-pressure air plug shock absorber, the fast extension work increases by 67.6%, thus, revealing the fast extension mechanism of the double-chamber shock absorber with high-pressure piston and successfully explaining the phenomenon of the fast extension ability exceeding the expectation of the shock absorber.